(untitled) (Journal of the College of Education for Women, 2019)
Targeted search current: 1- Know the support and justice teachers at junior high school students. 2 - Know the differences in support and justice teachers at junior high school students according to variable sex (male, female). 3- know the level of ambition at the junior highschool students. 4- know the differences in the level of ambition according to the gender variable (males, females). 5- Know the correlation between support and justice teachers and the level of ambition. Sample consisted of (200) students were chosen from the research community the original randomly by (100) males and (100) females. The Adata Search has the researcher prepared scale support and justice teachers by providing identification is open to students and refer to the theoretical literature and previous studies, and the second tool researcher has adopted a measure Bader (2005). The researcher using a number of statistical tools, including test Altaúa for one sample and two independent samples in addition to the use of Pearson’s correlation coefficient results showed that teachers provide support and justice for students, and that teachers provide support and justice for males than females, and the results showed that the sample has a level of ambition, and he There is no significant difference in the level of ambition according to the gender variable, as the results showed a correlation between support and justice teachers and the level of ambition, and this results reached researcher to a number of recommendations and proposals11